Storytelling, special needs and disabilities : practical approaches for children and adults - Grove, Nicola, 1948- (Routledge, Taylor & Francis Group, 2022)
"Now in a fully revised and updated second edition, this innovative and wide-ranging book shows how storytelling can open new worlds for individuals with special educational needs and disabilities. Providing a highly accessible combination of theory and practice, the contributors to this book define their own approaches to inclusive storytelling, describing the principles and theory that underpin their practice, whilst never losing sight of the joy at the heart of their work. Topics include therapeutic storytelling; language and communication; interactive and multi-sensory storytelling, and technology. Each chapter includes top tips, and signposts further training for practitioners who want to start using stories in their own work, making this book a crucial and comprehensive guide to storytelling practice with diverse learners. This new edition: Has been fully updated to reflect the way in which this field of storytelling has grown and developed, Uses a broad range of chapters, structured in a way that guides the reader through the conceptualisation of a storytelling approach towards its practical application. Includes an additional chapter, sharing the lived experiences of storytellers who identify as having a disability. Full of inspiring ideas to be used with people of all ages and with a range of needs, this book will be an invaluable tool for education professionals, as well as therapists, youth workers, counsellors and theatre practitioners working in special education"- Resumé vydavatele
"First edition published by Routledge 2012" -- Title page verso.
Keywords: vyprávění; speciální pedagogika; storytelling; special education; elektronické knihy; sborníky; electronic books; papers of several authors